Wave radiation from a truncated cylinder of arbitrary cross section. (1st February 2019) - Yu, Huifeng; Zheng, Siming; Zhang, Yongliang; Iglesias, Gregorio
Abstract: In this paper, a semi-analytical model for solving wave radiation from a truncated cylinder of arbitrary cross section is presented based on linear potential flow theory. The water domain is divided into the interior domain beneath the cylinder and the exterior domain outside the vertical cylinder column. Radiated spatial potentials in these subdomains are expressed as a series expansion of eigen-functions using the method of separation of variables. The continuity conditions for pressure and velocity are satisfied at the interface of the two domains, where the Fourier series expansion method is employed to deal with the radius function associated terms. Therefore, the unknown coefficients in the radiated potential expressions are determined by means of the eigen-function matching method. Hydrodynamic coefficients of the truncated cylinder are evaluated directly based on the radiated spatial potentials. Case studies on wave radiation from a truncated cylinder with "cosine" and "circular" cross sections show a good agreement between the semi-analytical results of added-mass/radiation damping and numerical ones/published data. The validated semi-analytical model is then adopted to study the hydrodynamic characteristics of truncated cylinders with "circular", "cosine", "elliptical" and "quasi-elliptical" sections. For the latter case, the influence of draft on wave radiation is also investigated. Highlights: Present a semi-analytical model of wave radiation by a truncated vertical cylinder. Prove symmetric property of the radiation force for cylinder with "cosine" section. Compare results of "circular", "cosine", "elliptical", "quasi-elliptical" sections. Explore the effect of draft for the cylinder with "quasi-elliptical" cross section.